Nurses’ knowledge and reported practice of palliative and end- of-life care nursing at the university college hospital, Ibadan, Nigeria (2014)
Background: Palliative and End-of-Life (EoL) care nursing is the active total care of patients with advanced illness. The goal of this approach to care is the achievement of the best quality of life for patients and their families. No member of the interdisciplinary team is more central to making these discoveries possible than the nurse. Care of patients with life-limiting diseases and dealing with death and dying is an integral part of oncology musing. In environments of best practice, nurses routinely identify and suggest patients to physicians for possible referral to palliative care and discuss potential referrals with families. Though studies from other parts of the globe had reported levels of knowledge and practice of palliative and EoL care amongst nurses; there is dearth of literature emanating from Nigeria, specifically on the knowledge and practice of palliative and EoL care nursing by professional nurses. To the best of the authors’ knowledge, the few that have been published in Nigeria, focused mainly on knowledge of palliative care among healthcare workers. Objective: The objective of this study was to explore the knowledge and reported practice of palliative and EoL care nursing by nurses working at the University College Hospital (UCH), Ibadan, Nigeria; in a bid to inform where gap in knowledge to practice may exist. Methods: This is a descriptive study utilizing cross-sectional design, 650 nurses in various nursing cadres, who were participating in the monthly continuing education program organized by the In- Service Education (ISE) department of UCH for nurses, over a period of twelve months. With the aid of a validated semi -structured questionnaire, information was elicited from the participants on demographic variables, education and training profile, and contents of nursing education curricula, years of working experience among others. On a 5-point Likert scale, their knowledge and principles of palliative and end-of-life care nursing were assessed. Their reported practice was also assessed. Results: The sample of 650 nurses was made up of 155(23.8%) university graduates and 495(76.2) diploma-prepared nurses. Three hundred and sixty four (32%) of the participants had component of palliative care nursing in their curricula, while 327(50.3%) had components of palliative care nursing and pain management in their curricula. Fifty-four (4.7%) had formal palliative care training post- qualification. Majority (81.2%) of the respondents claimed they apply the knowledge and principles of palliative care in their current practice. A little above fifty-nine percent (59.2%) had good knowledge of palliative care. However, the practice of some was poor (40.0%) and many (29.2%) also had poor attitude towards provision of palliative and EoL care to patients who are approaching EoL; evidenced by their inappropriate responses to the related questions. Conclusion: This study identified gaps in nursing knowledge and reported practice as it relates to palliative and EoL care nursing in the management of life-limiting diseases, such as cancer. It has provided the authors with baseline data that will be used to generate additional studies to further advocate for the need to integrate palliative and EoL care nursing components into nursing education curricula, both at the university and diploma levels. Our findings suggest a need for urgent review of nursing education curricula in Nigeria at both levels, and the input of all stakeholders especially the Nursing & Midwifery Council of Nigeria